New MAC protocol for broadband multimedia satellite networks - LIU Jian-you; GUO Qing; LIU Gong-liang (Tongxin xuebao)
A new MF-TDMA based MAC protocol,called CRRAP（combined reservation and random access protocol）,was proposed for broadband multimedia satellite networks.It adopted combined random and piggy-backed reservation,combined demand assignment and free assignment.Simulation results show that CRRAP can reduce end-to-end delay in high system load situation,which contribute to throughput performance.In addition,it achieves high bandwidth utiliza-tion.